Homo Complexus: Edgar Morin’s Holistic Reconceptualization of Human Nature in La Méthode 5 - Wiguna, Ida Bagus Alit Arta; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman; Suastra, I Wayan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The prevailing philosophical and anthropological concepts of Homo Sapiens, Homo Faber, and Homo Economicus have historically understood humanity through a single, dominant trait. This reductionism fails to capture the inherent complexity of human nature. Through a qualitative content analysis of Edgar Morin’s La Méthode 5: L’Humanité de L’Humanité, this study elucidates Morin’s concept of Homo Complexus as a corrective framework. The findings reveal that Morin posits human nature as a productive, Yin-Yang-like tension between rationality (Homo Sapiens) and irrationality/emotion (Homo Demens), where these poles are interdependent and complementary. The study concludes that Homo Complexus provides a more holistic and realistic foundation for understanding human identity, with significant implications for fields like education, which must now account for the full spectrum of rational, emotional, mythical, and aesthetic human dimensions. In this study, a literature review method with a qualitative descriptive research approach is used, discussing primary sources from Edgar Morin’s book and secondary sources from books that discuss the concepts of Homo Sapiens, Homo Faber, Homo Ludens, and Homo Economicus. The findings of the study show that human beings, according to Morin, cannot be understood through only one dimension of their existence but as a combination of elements that interact with each other, such as rationality, emotions, myths, art, and affectivity. The concept of Homo Complexus challenges conventional views that separate humans into narrow categories and offers a more complete understanding of humans. This research has contributed to introducing a humanist and holistic integrative approach in human philosophy. The findings of this research in the field of social sciences provide a new view of humans living complex and dynamic lives.